Substance P Induces CCN1 Expression via Histone Deacetylase Activity in Human Colonic Epithelial Cells - Koon, Hon Wai (American Society for Investigative Pathology, 2011)
We have shown that substance P (SP) and its neurokinin-1 receptor (NK-1R) regulate intestinal angiogenesis by increasing expression of protein CYR61 (the cysteine-rich angiogenic inducer 61, or CCN1) in colonic epithelial cells. However, the mechanism involved in SP-induced CCN1 expression has not been studied, and the outcome of increased CCN1 expression in the development of colitis is not fully understood. Because histone deacetylase (HDAC) modulates transcription of several genes involved in inflammation, we investigated participation of HDAC in SP-induced CCN1 expression in human colonic epithelial NCM460 cells overexpressing NK-1R (NCM460-NK-1R) and in primary colonocytes. SP increased HDAC activity with deacetylation and dephosphorylation of nucleosome protein histone H3 in NCM460-NK-1R and/or primary colonocytes. Histone deacetylation and dephosphorylation was observed in colonic mucosa from irritable bowel disease patients. Similarly, colonic mucosal tissues from mice exposed to dextran sulfate sodium showed histone H3 deacetylation and dephosphorylation and increased HDAC activity that was reversed by the NK-1R antagonist CJ-12255. SP-induced increased CCN1 expression in NCM460-NK-1R cells was abolished by pharmacological HDAC inhibition. HDAC overexpression activated basal and SP-induced CCN1 promoter activity. Intracolonic CCN1 overexpression significantly ameliorated dextran sulfate sodium-induced colitis, with reduction of proinflammatory cytokine expression in mice. Thus, SP-mediated CCN1 expression in the inflamed human and mouse colon involves increased HDAC activity. Our results strongly suggest that increased CCN1 expression may be involved in mucosal healing during colitis.